(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The goal of this research is to analyze the papers published in the chosen journals, focusing ontheir content and bibliometric metrics. The study of academic books and the development of librarycataloging software are two of Library and Information Science’s most important facets. Scientometricsexamines all facets of the study of scientific literature and its approaches, tactics, and models, D-LibMagazine, on the other hand, is dedicated to digital innovation and the digital dissemination of librarymaterials. The journal D-Lib is dedicated to digital libraries, whereas the periodical Scientometricsincludes scientometrics, bibliometrics, and webometrics.